Knowledge, Attitude, and Implementation toward Denture Adhesive among Indonesian Dental Students and Dentists - Mursid, Saraventi; Annisa; Larasati, Astari (Indonesia Prosthodontic Association, 2024)
ABSTRACT Introduction: Increased exposure of denture adhesive commercially may have impact on how denture wearers use this material without dentist’s prescription. Dentists need to know the proper use of denture adhesive so that they can educate public the indication and contraindication to avoid side effects. The aim of this study was to assess knowledge, attitudes, and implementation toward of denture adhesive among dental students and dentists. Methodology: The questionnaire was made through expert discussion and psychometric test to determine the validity and reliability of the questionnaire was tested on 146 subjects consist of 73 dental students and 73 dentists in Jakarta. Test retest reliability was tested on 30 subjects. Univariate analyze were carried out on knowledge, attitudes, and implementation of each group of respondents. Result: The 29 items of questionnaires were consist of three domains of knowledge (23 items), attitude(3 items) and implementation (3 items). Convergent validity was confirmed by correlation coefficients ranged from 0.327 to 0.355 for knowledge, attitude, and implementation domain. Internal consistency showed Cronbach alpha values from 0,669 to 0,859. The interclass correlations were ranged form 0.821-0.923. Significant differences between dental students and dentists were found for implementation domain toward denture adhesive. In this study, 87.7% dental students and 80.8% dentists were already know about denture adhesive. But 78.1% dental students and 39.7% dentists have never applied this material. Conclusions: Questionnaire knowledge, attitude, and implementation toward denture adhesive in Indonesian has a good validity and reliability value, especially in knowledge and implementation domain. The majority of respondents in the dental student and dentist groups already know about indications and contraindications toward denture adhesive.